The acute effects of cannabis, with and without cannabidiol, on attentional bias to cannabis related cues: a randomised, double-blind, placebo-controlled, cross-over study - Daniel Hall; Will Lawn; Shelan Ofori; Katie Trinci; Anya Borissova; Claire Mokrysz; Kat Petrilli; Michael A. P. Bloomfield; Matthew B. Wall; Tom P. Freeman; H. Valerie Curran (Psychopharmacology, 2024)
Rationale Attentional bias to drug-related stimuli is hypothesised to contribute towards addiction. However, the acute effects of Δ9-tetrahydrocannabinol (THC) on attentional bias to cannabis cues, the differential response in adults and adolescents, and the moderating effect of cannabidiol (CBD) are unknown. Objectives Our study investigated (1) the acute effects of vaporised cannabis on attentional bias to cannabis-related images in adults and adolescents and (2) the moderating influences of age and CBD. Methods We conducted a randomised, double-blind, placebo-controlled, cross-over study where three weight-adjusted vaporised cannabis preparations: ‘THC’ (8 mg THC for a 75-kg person), ‘THC + CBD’ (8 mg THC and 24 mg CBD for a 75-kg person) and PLA (matched placebo). Cannabis was administered on 3 separate days to 48 participants, who used cannabis 0.5–3 days/week: 24 adolescents (12 females, aged 16–17) and 24 adults (12 females, aged 26–29). Participants completed a visual probe task with cannabis cues. Our primary outcome was attentional bias to cannabis stimuli, measured using the differential reaction time to a cannabis vs. neutral probe, on 200-ms trials. Results In contrast to hypotheses, attention was directed away from cannabis cues on placebo, and there was a main effect of the drug ( F (2,92) = 3.865, p = 0.024, η 2 p = 0.077), indicating THC administration eliminated this bias. There was no significant impact of CBD nor an age-by-drug interaction. Conclusions Acute THC intoxication eliminated attentional bias away from cannabis cues. There was no evidence of differential response in adolescents compared to adults and no evidence that a moderate vaporised dose of CBD altered the impact of cannabis on attentional bias. Trial registration This study was listed with the US National Library of Medicine and registered on ClinicalTrials.gov, URL: Do Adolescents and Adults Differ in Their Acute Response to Cannabis?—Full Text View—ClinicalTrials.gov , registration number: NCT04851392.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Comparison of Oyster Aquaculture Methods and Their Potential to Enhance Microbial Nitrogen Removal From Coastal Ecosystems - Paraskevi Mara; Virginia P. Edgcomb; Taylor R. Sehein; David Beaudoin; Chuck Martinsen; Christina Lovely; Bridget Belcher; Rebecca Cox; Meghan Curran; Claire Farnan; Peter Giannini; Sarah Lott; et al. (Frontiers in Marine Science, 2021)
Coastal ecosystems are impacted by excessive nutrient inputs that cause degradation of water quality and impairments of ecosystem functioning. Regulatory and management efforts to enhance nutrient export from coastal ecosystems include sustainable oyster aquaculture that removes nitrogen in the form of oyster biomass and increases particulate export to underlying sediments where increased organic material may enhance microbial denitrification. To better understand the impacts of oyster aquaculture on nitrogen removal, we examined bacterial processes in sediments underlying three of the most common aquaculture methods that vary in the proximity of oysters to the sediments. Sediment samples underlying sites managed with these different aquaculture methods were examined using the 16S rRNA gene to assess microbial community structure, gene expression analyses to examine nitrogen and sulfur cycling genes, and nitrogen gas flux measurements. All sites were located in the same hydrodynamic setting within Waquoit Bay, MA during 2018 and 2019. Although sediments under the different oyster farming practices showed similar communities, ordination analysis revealed discrete community groups formed along the sampling season. Measured N 2 fluxes and expression of key genes involved in denitrification, anaerobic ammonium oxidation (anammox), and dissimilatory nitrate reduction to ammonium (DNRA) increased during mid-summer and into fall in both years primarily under bottom cages. While all three oyster growing methods enhanced nitrogen removal relative to the control site, gene expression data indicate that the nitrogen retaining process of DNRA is particularly enhanced after end of July under bottom cages, and to a lesser extent, under suspended and floating bags. The choice of gear can also potentially increase processes that induce nitrogen retention in the form of ammonia in the underlying sediments over time, thus causing deviations from predicted nitrogen removal. If nitrogen removal is a primary objective, monitoring for these shifts is essential for making decisions about siting and size of aquaculture sites from year to year.

Editorial: Reporting guidelines for psychopharmacology - Thomas Steckler; H. Valerie Curran; Harriet de Wit; Oliver Howes; Daniel Hoyer; Irwin Lucki; Klaus A. Miczek; A. Leslie Morrow; Lawrence H. Price; Trevor W. Robbins (Psychopharmacology, 2016)

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

Negative fire feedback in a transitional forest of southeastern Amazonia - JENNIFER K. BALCH; DANIEL C. NEPSTAD; PAULO M. BRANDO; LISA M. CURRAN; OSVALDO PORTELA; OSWALDO De CARVALHO; PAUL LEFEBVRE (Global Change Biology, 2008)
Anthropogenic understory fires affect large areas of tropical forest, particularly during severe droughts. Yet, the mechanisms that control tropical forests' susceptibility to fire remain ambiguous. We tested the widely accepted hypothesis that Amazon forest fires increase susceptibility to further burning by conducting a 150 ha fire experiment in a closed‐canopy forest near the southeastern Amazon forest–savanna boundary. Forest flammability and its possible determinants were measured in adjacent 50 ha forest plots that were burned annually for 3 consecutive years (B3), once (B1), and not at all (B0). Contrary to expectation, an annual burning regime led to a decline in forest flammability during the third burn. Microclimate conditions were more favorable compared with the first burn (i.e. vapor pressure deficit increased and litter moisture decreased), yet flame heights declined and burned area halved. A slight decline in fine fuels after the second burn appears to have limited fire spread and intensity. Supporting this conclusion, fire spread rates doubled and burned area increased fivefold in B3 subplots that received fine fuel additions. Slow replacement of surface fine fuels in this forest may be explained by (i) low leaf litter production (4.3 Mg ha −1 yr −1 ), half that of other Amazon forests; and (ii) low fire‐induced tree and liana mortality (5.5±0.5% yr −1 , SE, in B3), the lowest measured in closed‐canopy Amazonian forests. In this transitional forest, where severe seasonal drought removed moisture constraints on fire propagation, a lack of fine fuels inhibited the intensity and spread of recurrent fire in a negative feedback. This reduction in flammability, however, may be short‐lived if delayed tree mortality or treefall increases surface fuels in future years. This study highlights that understanding fuel input rate and timing relative to fire frequency is fundamental to predicting transitional forest flammability – which has important implications for carbon emissions and potential replacement by scrub vegetation.

Effects of partial throughfall exclusion on the phenology of Coussarea racemosa (Rubiaceae) in an east-central Amazon rainforest - Paulo Brando; David Ray; Daniel Nepstad; Gina Cardinot; Lisa M. Curran; Rafael Oliveira (Oecologia, 2006)

Woody debris contribution to the carbon budget of selectively logged and maturing mid-latitude forests - Wendy H. Liu; David M. Bryant; Lucy R. Hutyra; Scott R. Saleska; Elizabeth Hammond-Pyle; Daniel Curran; Steven C. Wofsy (Oecologia, 2006)

Tropical Deforestation and the Kyoto Protocol - Márcio Santilli; Paulo Moutinho; Stephan Schwartzman; Daniel Nepstad; Lisa Curran; Carlos Nobre (Climatic Change, 2005)

Vertical movements of bigeye tuna ( Thunnus obesus ) associated with islands, buoys, and seamounts near the main Hawaiian Islands from archival tagging data - Michael K. Musyl; Richard W. Brill; Christofer H. Boggs; Daniel S. Curran; Thomas K. Kazama; Michael P. Seki (Fisheries Oceanography, 2003)
To learn more about the movement patterns of bigeye tuna ( Thunnus obesus ), we deployed archival tags on 87 fish ranging in fork length from 50 to 154 cm. Thirteen fish were recaptured, from which 11 archival tags were returned, representing in aggregate 943 days‐at‐liberty. We successfully retrieved data from 10 tags, representing 474 days in aggregate. The largest fish recaptured was 44.5 kg [131 cm fork length (FL)] and the smallest 2.8 kg (52 cm). The deepest descent recorded was 817 m, the coldest temperature visited 4.7°C, and minimum oxygen level reached ∼1 mL L −1 . Fish spent little time at depths where water temperatures were below 7°C and oxygen levels less than ∼2 mL L −1 . Five fish were recaptured near the offshore weather buoy where they were tagged. Based on vertical movement patterns, it appeared that all stayed immediately associated with the buoy for up to 34 days. During this time they remained primarily in the uniform temperature surface layer (i.e. above 100 m). In contrast, fish not associated with a floating object showed the W‐shaped vertical movement patterns during the day characteristic of bigeye tuna (i.e. descending to ∼300–500 m and then returning regularly to the surface layer). Four fish were tagged and subsequently recaptured near Cross Seamount up to 76 days later. These fish exhibited vertical movement patterns similar to, but less regular than, those of fish not associated with any structure. Bigeye tuna appear to follow the diel vertical movements of the deep sound scattering layer (SSL) organisms and thus to exploit them effectively as a prey resource. Average night‐time depth was correlated with lunar illumination, a behaviour which mimics movements of the SSL.